UPACARA TEING NGASANG DALAM TRADISI MASYARAKAT MANGGARAI DAN SAKRAMEN BAPTIS (Sebuah Pengantar Studi Perbandingan Inisiasi) - Jagom, Bonifasius (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
For the etnic society of Manngarai, West Folres, the presence of child/baby in their family is a gift from God that must be grateful. The thanksgiving ceremony for the presence of the child is called Teing Ngasang. Teing Ngasang is a rite of giving a name to a child who born into the Manggarai people. For the name is something very valuable. Name is a representation of a person's personality. The